Comparative Analysis of Sharia Stock Screening Methods in Indonesia, Malaysia, and the United States - Eva Nurul Huda; Priyonggo Suseno (Maliki Islamic Economics Journal, 2023)
This study aims to find out and understand how the sharia stock screening model applies in Indonesia, Malaysia, and the United States and find a harmonization solution. The method used in this study is descriptive-qualitative through a literature study approach. Research data was obtained from various sources both online and offline, such as journal articles, books, and websites related to the screening of Sharia-compliant stocks, to be further analyzed using the content analysis method. The results show that there are differences in the screening criteria for sharia stocks on the Indonesian Stock Exchange, the Malaysian Stock Exchange, and the American Stock Exchange, both qualitatively and quantitatively. This difference is seen as a natural thing in Islamic teachings because it is in the realm of muamalah fiqh, which of course is adapted to the conditions of the people of each country. However, it is necessary to consider generalizing the implementation of strict and uniform sharia stock screening in order to increase understanding, interaction, and economic cooperation among Muslim countries at the global level.